BRCA1/2 alterations and reversion mutations in the area of PARP inhibitors in high grade ovarian cancer: state of the art and forthcoming challenges - Collet, Laetitia; Hanvic, Brunhilde; Turinetto, Margherita; Treilleux, Isabelle; Chopin, Nicolas; Le Saux, Olivia; Ray-Coquard, Isabelle (Frontiers in Oncology, 2024)
BRCA1/2 genes are part of homologous recombination (HR) DNA repair pathways in charge of error-free double-strand break (DSB) repair. Loss-of-function mutations of BRCA1/2 genes have been associated for a long time with breast and ovarian cancer hereditary syndrome. Recently, polyadenosine diphosphate–ribose polymerase inhibitors (PARPi) have revolutionized the therapeutic landscape of BRCA1/2-mutated tumors, especially of BRCA1/2 high-grade serous ovarian cancer (HGSC), taking advantage of HR deficiency through the synthetic lethality concept. However, PARPi efficiency differs among patients, and most of them will develop resistance, particularly in the relapse setting. In the current proposal, we aim to review primary and secondary resistance to PARPi in HGSC owing to BRCA1/2 alterations. Of note, as several mechanisms of primary or secondary resistance to PARPi have been described, BRCA1/2 reversion mutations that restore HR pathways are by far the most reported. First, the type and location of the BRCA1/2 primary mutation have been associated with PARPi and platinum-salt sensitivity and impact the probability of the occurrence and the type of secondary reversion mutation. Furthermore, the presence of multiple reversion mutations and the variation of allelic frequency under treatment underline the role of intratumor heterogeneity (ITH) in treatment resistance. Of note, circulating tumor DNA might help us to detect and characterize reversion mutations and ITH to finally refine the treatment strategy. Importantly, forthcoming therapeutic strategies, including combination with antiangiogenics or with targeted therapies, may help us delay and overcome PARPi resistance secondary to BRCA1/2 reversion mutations. Also, progression despite PARPi therapy does not preclude PARPi rechallenge in selected patients.